1992
DOI: 10.1097/00006842-199209000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stress and blood type on cortisol and VLDL toxicity preventing activity.

Abstract: Past research has associated ABO blood type and mental stress with cardiovascular risk. We studied the effects of blood type (A vs. O) coupled with a mirror drawing stressor on very low density lipoprotein toxicity-preventing activity (TxPA) and plasma cortisol levels. Exposure to the stressor significantly decreased TxPA and increased cortisol for the total group of 25 older adult males. However, the stress response patterns of the 15 blood type A males were different from those of the 10 type O subjects. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…This leaves the association between a possible expression of blood-type antigens on human sensory neurons open to speculation. Another, older study found an association between blood type and timecourse plasma levels of the "stress hormone" cortisol, which had been experimentally raised in study participants in response to an artificial stressor (Neumann et al, 1992). In this study 'A' adults were found to have a quicker recovery from the hormonal upregulation, but, at the same time, had also higher absolute levels of cortisol than 'O' adults at all stages of the experimental manipulation.…”
Section: -Discussionmentioning
confidence: 45%
“…This leaves the association between a possible expression of blood-type antigens on human sensory neurons open to speculation. Another, older study found an association between blood type and timecourse plasma levels of the "stress hormone" cortisol, which had been experimentally raised in study participants in response to an artificial stressor (Neumann et al, 1992). In this study 'A' adults were found to have a quicker recovery from the hormonal upregulation, but, at the same time, had also higher absolute levels of cortisol than 'O' adults at all stages of the experimental manipulation.…”
Section: -Discussionmentioning
confidence: 45%
“…7 Researchers believe this could be due to the correlation between blood type AB and blood clots, as well as, higher rates of inflammation that have also been linked to type AB and B blood types. 8 A survey also states that most of the mentally disturbed people by birth or later half of their life are mostly found A+ and AB+. As most of the organizations find it not to disclose the blood group of their patients Therefore it is very hard to get the data whereas, in person we also have noted that it is being said AB+ and A+ are highly weak in sense organs.…”
Section: Discussionmentioning
confidence: 99%
“…Neumann et al found strong association between 'A' and 'O' blood group with stress response, similar to our findings. He also stated that the 'A' blood group had higher initial levels of low density lipoprotein toxicity-preventing activity (TxPA) and cortisol as well as quicker stress recovery rates than the type 'O' group [22]. [24].…”
Section: Discussionmentioning
confidence: 99%